[PP.02.15] EFFICIENCY OF BISOPROLOL IN THE TREATMENT OF STAGE I HYPERTENSION "BIPREZ" STUDY. (September 2017) - Stojanov, V.; Radivojevic, N.; Paunovic, K.; Jakovljevic, B.
Abstract : Objective: The aim was to assess the efficiency and safety of bisoprolol therapy in patients with Stage I hypertension in three doses; 2.5 mg, 5 mg, and 10 mg. Design and method: A cross-sectional study comprised 9060 patients (65% women and 35% men) with stage I arterial hypertension, aged 61.6 ± 11.5 years. Blood pressure (BP) was measured by an oscillometric device at the beginning of the study, and after three months of therapy. The treatment initiated with 2.5 mg bisoprolol; the dose was increased to 5 mg after two weeks in persons who failed to decrease blood pressure adequately; the dose was increased to 10 mg after further 4 weeks in persons whose blood pressure remained increased. Patients were followed up for 8 weeks in total. Blood glucose, total cholesterol, and triglycerides were measured with standard biochemical procedures. The differences in blood pressure values after eight-week therapy in comparison to the baseline were tested with Student's t-test for paired samples. Results: Mean systolic blood pressure (SPB) at the beginning of the study was 141.1 mmHg; mean diastolic blood pressure (DBP) was 90.5 mmHg. After eight weeks of therapy, mean SBP was significantly reduced to 128.9 mmHg (p < 0.01), and DBP was significantly reduced to 79.0 mmHg (p < 0.01). At the end of the eight-week treatment, 27.8% of the patients had normal blood pressure, 51.5% had prehypertension, and 20.7% still had stage I hypertension. The therapy lead to significant decrease of heart rate from 82.2 beats/min to 71 beats/min (p < 0.01), as well as to decrease of the following biochemical parameters: glucose (from 6.05 mmol/l to 5.83 mmol/l), total cholesterol (from 5.97 mmol/l to 5.73 mmol/l), LDL-cholesterol (from 3.65 mmol/l to 3.46 mmol/l) and triglycerides (from 1.96 mmol/l to 1.82 mmol/l) (all p < 0.01). Conclusions: Eight-week therapy with bisoprolol not only reduces blood pressure and heart rate in hypertensive men, but decreases glucose, cholesterol and triglyceride levels, and is metabolically neutral as well.